PEMBANGUNAN PERTANIAN PADI DI KAMBOJA - Mayasuri Presilla; Rucianawati Rucianawati; Dina Srirahayu (Jurnal Kajian Wilayah, 2019)
Cambodia is one of the ten largest rice exporting countries in the world market.  Although its reputation is not as great as those of Thailand and Vietnam, the growth of rice production and export is worth to be reckoned.  In one decade, an increase of rice production by nine percent per year was followed by an increase of rice export each year.  This proves that Cambodia has succeed to struggle from its adversity due to war and colonialism.  However, it cannot be denied that Cambodia still faces diverse obstacles in increasing rice production.  With all of its limitations, Cambodia has tried to use its resources and collaboration networks as the means to address those obstacles.  By looking at the historical and sociological aspects, this study provides a comprehensive picture of rice development in Cambodia, which places more emphasis on recent obstacles and efforts in rice farming.